2022
DOI: 10.1111/ijcs.12834
|View full text |Cite
|
Sign up to set email alerts
|

Attachment styles and customers' long‐term relationships in a service context

Abstract: The main objective of this study is to use attachment styles theory to explore long-term relationships in a service context using the mobile market as a case study. Attachment theory focuses on the primary link between maternal loss or deprivation and later personality development. This theory was extended to adult life and commercial contexts. Three attachment styles (secure, avoidant, and anxious) were used as the independent variables. Commitment and trust, as constructs of any relationship, were employed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 109 publications
0
0
0
Order By: Relevance
“…Moreover, a number of empirical research have demonstrated that the trust component positively affects corporate performance (Roy et al 2020) and customer loyalty (Raduzzi, 2019, Ibrahim et al, 2020. Frydman and Moliner (2022) emphasize the significance of loyalty and cooperation in relationships, stating, "...with absence of trust and commitment, there can be no partnership." In the relationship literature, trust and commitment are typically discussed together, with very few researchers considering one without the other.…”
Section: B Trustmentioning
confidence: 99%
“…Moreover, a number of empirical research have demonstrated that the trust component positively affects corporate performance (Roy et al 2020) and customer loyalty (Raduzzi, 2019, Ibrahim et al, 2020. Frydman and Moliner (2022) emphasize the significance of loyalty and cooperation in relationships, stating, "...with absence of trust and commitment, there can be no partnership." In the relationship literature, trust and commitment are typically discussed together, with very few researchers considering one without the other.…”
Section: B Trustmentioning
confidence: 99%